TPACK Theoretical Correspondence with Learning Variables and Its Application Effectiveness in Learning - Parwati, Ni Nyoman; Suharta, I Gusti Putu; Sudatha, I Gde Wawan (Journal of Pedagogy and Education Science, 2023)
The role of educational technology is to facilitate people to learn more efficiently to achieve optimal learning outcomes. One thing that can be done is to promote learning using learning media. However, this learning media will be effective with the right learning strategy. This study aimed to describe the correspondence of the TPACK framework with learning variables in educational technology in the digital era based on literature studies of the effectiveness of implementing the flipped classroom learning strategy assisted by virtual laboratory media on understanding mathematical concepts through pre-experimental studies. The subjects of this study were researchers, teachers, and 8th-grade students of SMPN 5 Abiansemal-Badung-Bali in the even semester of the academic year 2022/2023. The data collection instrument was a test of understanding mathematical concepts. Literature study data analysis was conducted by searching relevant theories and collecting articles, data reduction, discussion, and conclusions. The pre-experimental study was carried out by calculating the value of the students' pre-test and post-test gain scores for understanding mathematical concepts. There is a description of the correspondence of the TPACK framework with learning variables in educational technology: Technology elements correspond to condition variables; Paedagogy corresponds to method; and content knowledge corresponds to the outcome variables. The gain score of understanding students' mathematical concepts by applying the flipped classroom assisted by the virtual laboratory obtained 28% of students achieving the high criteria, 48% attaining moderate criteria, and 24% receiving low criteria. Thus, the flipped classroom learning strategy assisted by virtual laboratory media effectively increases students' understanding of mathematical concepts.